ISLANDS OF INNOVATION: EXAMINING THE NEXUS BETWEEN CULTURALLY RESPONSIVE RELATIONSHIPS AND COGNITIVELY DEMANDING ACADEMIC DISCOURSE - Moon, Michael W (East Carolina University, 2023)
The purpose of the study was to examine the extent to which participants built meaningful culturally and linguistically responsive (CLR) relationships with students and to what extent those same participants engaged in cognitively demanding academic discourse with their students. The participatory action research (PAR) study took place in a rural middle school in eastern North Carolina serving approximately 550 students in grades 6-8 over a period of two academic years from Fall 2021 to Fall 2022. The co-practitioner researcher (CPR) team comprised four eighth-grade teachers and the school principal as lead researcher. The CPR team met biweekly as an Equity-Centered Networked Improvement Community (EC-NIC) (Bryk et al., 2015) and engaged in three cycles of inquiry using Community Learning Exchange methodology and pedagogy (Guajardo et al., 2016) to develop their knowledge, skills, and dispositions as warm demanders (Delpit, 2012; Kleinfeld, 1975; Ladson-Billings, 2009; Ware, 2006) in support of equitable, cognitively demanding academic discourse (Resnick et al., 2015; Vygotsky, 1978; Zwiers, 2007). The findings from the PAR study revealed: (1) Participants demonstrated high empathy but inconsistently high expectations; (2) when a teacher is a warm demander, cognitively demanding academic discourse is much more likely to occur; and (3) teachers created islands of innovation (Fullan, 2001) or pockets of success to develop culturally responsive relationships with students and develop discourse opportunities. The study has implications for principals, teachers, and other school leaders to develop school-wide systems of support to improve their internal capacity for facilitating EC-NICs to cultivate CLR relationships and cognitively demanding academic discourse.
Keywords: culturally and linguistically responsive; warm demanders; academic discourse; participatory action research; equity; communities of practice; networked improvement community; community learning exchange; Culturally relevant pedagogy--North Carolina; Rural schools--North Carolina; Middle school students--North Carolina--Attitudes; Teacher-student relationships; Educational equalization